β-lapachone suppresses tumour progression by inhibiting epithelial-to-mesenchymal transition in NQO1-positive breast cancers - Yang Yang (Nature Portfolio, 2017)
Abstract NQO1 is a FAD-binding protein that can form homodimers and reduce quinones to hydroquinones, and a growing body of evidence currently suggests that NQO1 is dramatically elevated in solid cancers. Here, we demonstrated that NQO1 was elevated in breast cancer and that its expression level was positively correlated with invasion and reduced disease free survival (DFS) and overall survival (OS) rates. Next, we found that β-lapachone exerted significant anti-proliferation and anti-metastasis effects in breast cancer cell lines due to its effects on NQO1 expression. Moreover, we revealed that the anti-cancer effects of β-lapachone were mediated by the inactivation of the Akt/mTOR pathway. In conclusion, these results demonstrated that NQO1 could be a useful prognostic biomarker for patients with breast cancer, and its bioactivatable drug, β-lapachone represented a promising new development and an effective strategy for indicating the progression of NQO1-positive breast cancers.